International financial reporting standards and experts’ perceptions of disclosure quality. - Daske, Holger; Gebhardt, Günther (Abacus)
From 2005, over 7,000 listed firms in the European Union and many more around the world are required to adopt International Financial Reporting Standards (IFRS). The introduction of a uniform accounting regime is expected to ensure greater comparability and transparency of financial reporting around the world. However, recent research has questioned the quality of financial statements prepared under IFRS standards, particularly in the presence of weak enforcement mechanisms and adverse reporting incentives (Ball et al., 2003). In this paper, we assess the quality of the financial statements of Austrian, German and Swiss firms which have already adopted internationally recognized standards (IFRS or U.S. GAAP). The study makes use of available disclosure quality scores extracted from detailed analyses of annual reports by reputed accounting scholars (‘experts’). This work complements other contemporary research on the quality of IFRS financial statements where the properties of earnings are used as an evaluation metric (Barth et al., 2005). Our evidence shows that disclosure quality has increased significantly under IFRS in the three European countries we analyse. This result holds not only for firms which have voluntarily adopted IFRS or U.S. GAAP, but also for firms which mandatorily adopted such standards in response to the requirements of specific stock market segments. Although we cannot establish direct causality due to the inherent self-selection issues for most of our sample firms, the evidence shows that the quality of financial reports has increased significantly with the adoption of IFRS.